2017
DOI: 10.1111/1752-1688.12560
|View full text |Cite
|
Sign up to set email alerts
|

Does the Temporal Resolution of Precipitation Input Influence the Simulated Hydrological Components Employing the SWAT Model?

Abstract: This study aimed to evaluate the influence of sub‐daily precipitation time steps on model performance and hydrological components by applying the Green and Ampt infiltration method using the Soil and Water Assessment Tool (SWAT). Precipitation was measured at a resolution of 0.1 mm and aggregated to 5‐, 15‐, 30‐, and 60‐min time steps. Daily discharge data over a 10‐year period were used to calibrate and validate the model. Following a global sensitivity analysis, relevant parameters were optimized through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…The positive PBIAS values indicate a slight underestimation of the measured discharge. Generally, the model performance was similar compared to other studies performed in the same catchment (Bauwe et al, , 2017.…”
Section: Hydrologysupporting
confidence: 78%
See 1 more Smart Citation
“…The positive PBIAS values indicate a slight underestimation of the measured discharge. Generally, the model performance was similar compared to other studies performed in the same catchment (Bauwe et al, , 2017.…”
Section: Hydrologysupporting
confidence: 78%
“…1. Parameter selection: Based on previous simulation studies in the same area (Bauwe et al, , 2017 we selected 27 parameters for sensitivity analysis. We performed a global sensitivity analysis using SWAT-CUP (SWAT-CUP 2012, version 5.1.6.2, Abbaspour, 2014).…”
Section: Modeling Approachmentioning
confidence: 99%
“…Finally, individual analysis performed in each scenario of the five watersheds, showed that land use is the variable with the highest impact on CN2, followed by the average slope. This close relation among land use and CN2 has been widely assessed in scientist literature (Amengual et al, 2015;Bauwe et al, 2017;Boongaling et al, 2018;Rozalis et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…into the effective hydraulic conductivity expression (Bauwe et al, 2017;Boithias et al, 2017;Jeong et al, 2010;Maharjan et al, 2013;Nearing et al, 1996;Neitsch et al, 2011). Flood propagation in channels was simulated using the Muskingum river routing method (Cunge, 1969;Overton, 1966) whose main expression is presented in Eq.…”
Section: Surface Runoff Flood Propagation and Velocity Of Flowmentioning
confidence: 99%
“…Similarly, Bauwe et al . () found that precipitation time step of < 1 h does not provide significant differences in SWAT output except for a scenario when the saturated hydraulic conductivity is low and the curve number is high.…”
mentioning
confidence: 95%